Alpha particle detection in high magnetic fields with applications in designing fission fragment rocket engine - Sandeep Puri; Cuikun Lin; Andrew Gillespie; Ian Jones; Christopher Carty; Mitchell Kelley; Ryan Weed; Robert V. Duncan (Scientific Reports)
Abstract We present recent experiments on an innovative alpha particle detection system, designed to investigate charged particle confinement and transport in high magnetic fields. Our test platform operates within a 3-T Siemens MRI superconducting magnet, providing a large cross-section (~ 40 cm diameter) for studying the behavior of charged particles in an aluminum vacuum can that is inserted into a uniform 3 T magnetic field. Using Americium-241 (241Am) sources placed inside this cylindrical vacuum chamber, we conducted simulations and experiments to measure and analyze alpha particle flux. This system enables the study of fundamental charged particle dynamics, which are relevant to a variety of applications, including nuclear propulsion concepts. Alpha particles serve as a surrogate for fission fragments due to their similar charge-to-mass ratio and comparable velocity, allowing us to explore key physical mechanisms that could influence the confinement and transport of fission fragments in future propulsion systems, specifically a fission fragment rocket engine (FFRE). This much more efficient nuclear rocket propulsion FFRE design was first proposed in the 1980s with the intent of greatly reducing transit times in long-duration space travel. Our objective is to enhance the operational efficiency of this nuclear rocket while gaining deeper insights into the behavior of fuel particles and of the fission-fragment ejecta within strong magnetic fields experimentally. The methodologies developed in this study establish a foundation for future experimental studies involving FFRE. More broadly, this work introduces a versatile approach for analyzing ion flux and nuclear reaction fragments across various experimental platforms.